A study of supervisory practices of chartered technical colleges in the Philippines and Thailand - Rung Poolswash 1937- (1968)
This study identified and compared the supervisory practices used in three Chartered Technical Colleges of the Philippines and of Thailand. Results show that both countries subscribe to the modern philosophy and goals of supervision, practice democratic processes in supervision, and both have limited library facilities, textbooks, equipment and other instructional materials. However, it is also concluded that supervisory practices in the Philippines is a little more advanced than Thailand, particularly in classroom observations and visitations.